Strawberry Potention as a Teeth Whitener - Frecilia Afrida (Jurnal Penelitian Perawat Profesional, 2020)
Teeth whitening or bleaching is a process that can make teeth whiter like the original color of teeth. Utilization of natural ingredients is popular today because it is safer, cheaper, and easier to obtain when compared to chemicals. One of the natural ingredients that can be used as a teeth whitener is for example strawberries. The purpose of this article is to find out the potential of strawberries as teeth whitening. This article was compiled by searching literature sources through NCBI and Google Scholar, totaling 17 articles published in 2005-2018 with the keywords strawberry, teeth whitening, and tooth bleaching. The analytical method used is systematic literature review (SLR), which identifies, studies, evaluates, and interprets all existing research with topic areas of interesting phenomena as well as certain relevant questions. The results of the article search found that strawberry has the potential to be an alternative to bleaching and produce significant color changes. This can happen because of the content of elegat acid () and malic acid () found in strawberries. In addition to the two ingredients, strawberries also have a low pH so they have the ability to whiten teeth better when compared to other fruits.